Epidemiological Profile of Intracerebral Hemorrhage during a 10-Year Period in a Southern Brazilian Region - Almeida, Timóteo Abrantes de Lacerda; Almeida, Fernanda Gabriella Bezerra de Araújo; Giacomini, Luidia Varrone; Niederauer, Andressa Gomes; Cho, Anna; Mallmann, Adroaldo B.; Camelo, Ricardo Macedo; Bertolin, Telma Elita (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Objective Spontaneous intracerebral hemorrhage is responsible for 20% of all cases of cerebrovascular accidents, which might lead to functional disabilities and death. There are few epidemiological data on spontaneous intracerebral hemorrhage in Brazil, and more specifically in the southern region of the country. Methods We reviewed data of 221 patients with intracerebral hemorrhage who attended our department between January of 2004 and December of 2013 and were registered as I61 and I62 according to the 10th edition of the International Classification of Diseases and Related Health Problems (ICD-10).Results From the 221 cases, 53.8% were male, and the median age was 63 years old. Arterial hypertension was reported in 62.4% of the patients. Surgical treatment was performed in 28.9% of all cases and pneumonia affected 19.9%. In 73.4% of the cases, the patients died or were severely disabled at discharge. We found an association of heart disease, coagulopathies, chronic kidney disease, anticoagulant drugs use, surgical treatment, and pneumonia with a poorer outcome.Conclusion The present study describes the epidemiological profile of intracerebral hemorrhage in a southern Brazilian population during a 10-year period.
Keywords: intracerebral hemorrhage; epidemiology; Brazil; cerebrovascular accident/stroke